A Label-Free Electrochemical Immunosensor for CEA Detection on a Novel Signal Amplification Platform of Cu2S/Pd/CuO Nanocomposites - Cao, Linlin; Zhang, Wen; Lu, Sumei; Guo, Chengjie; Wang, Peijun; Zhang, Dantong; Ma, Wanshan (Frontiers in Bioengineering and Biotechnology, 2021)
Cancer embryonic antigen (CEA) is regarded as one of crucial tumor markers for colorectal cancer. In this study, we developed the snowflake Cu2S/Pd/CuO nanocomposite to construct an original label-free electrochemical immunosensor for the ultrasensitive detection of CEA levels. The nanocomposite of cuprous sulfide (Cu2S) with Pd nanoparticles (Pd NPs) was synthesized through an in situ formation of Pd NPs on the Cu2S. Cuprous sulfide (Cu2S) and CuO can not only be used as a carrier to increase the reaction area but also catalyze the substrate to generate current signal. Palladium nanoparticles (Pd NPs) have excellent catalytic properties and good biocompatibility, as well as the ability of excellent electron transfer. The immunosensor was designed using 5 mmol/L H2O2 as the active substrate by optimizing the conditions with the detection range of 100 fg/mL to 100 ng/mL and the minimum detection limit of 33.11 fg/mL. The human serum was detected by electrochemical immunoassay and the results were consistent with the commercial electrochemical immunosensor. Therefore, the electrochemical immunosensor can be used as the detection of human serum samples, and have potential value for the clinical application.